The gut microbiome as a potential source of non-invasive biomarkers of chronic obstructive pulmonary disease - Li, Naijian; Yi, Xinzhu; Chen, Chiyong; Dai, Zhouli; Deng, Zhishan; Pu, Jinding; Zhou, Yumin; Li, Bing; Wang, Zhang; Ran, Pixin (Frontiers in Microbiology, 2023)
The link between gut microbial dysbiosis and the development of chronic obstructive pulmonary disease (COPD) is of considerable interest. However, little is known regarding the potential for the use of the fecal metagenome for the diagnosis of COPD.Methods: A total of 80 healthy controls, 31 patients with COPD severity stages I or II, and 49 patients with COPD severity stages III or IV fecal samples were subjected to metagenomic analysis. We characterized the gut microbiome, identified microbial taxonomic and functional markers, and constructed a COPD disease classifier using samples.The fecal microbial diversity of patients with COPD stages I or II was higher than that of healthy controls, but lower in patients with COPD stages III or IV. Twentyone, twenty-four, and eleven microbial species, including potential pathogens and proinflammatory bacteria, were significantly enriched or depleted in healthy controls, patients with COPD stages I or II, and patients with COPD stages III & IV. The KEGG orthology (KO) gene profiles derived demonstrated notable differences in gut microbial function among the three groups. Moreover, gut microbial taxonomic and functional markers could be used to differentiate patients with COPD from healthy controls, on the basis of areas under receiver operating characteristic curves (AUCs) of 0.8814 and 0.8479, respectively. Notably, the gut microbial taxonomic features differed between healthy individuals and patients in stages I-II COPD, which suggests the utility of fecal metagenomic biomarkers for the diagnosis of COPD (AUC=0.9207).Conclusions: Gut microbiota-targeted biomarkers represent potential non-invasive tools for the diagnosis of COPD.